Occupational Hand Eczema Among Housewives Attending Baquba Teaching Hospital - Al-Azzawi , Shahab A (Diyala Journal of Medicine, 2019)
Background: Housewife's hand eczema is a common disease which is due to the excessive and prolonged exposure of the hands to soap and water. Patients with hand eczema frequently have a history of atopic dermatitis or atopy. Aims: To determine the, clinical features, and patterns of occupational housewife's hand eczema in housewives and its prevalence in patients with atopic eczema or atopy attending Baquba teaching hospital. Patients and Methods: A cross-sectional study carried out in 1st June 2012 till 31st May 2013 among random sample of (280) housewives, aged (18-48) years, to determine the prevalence of occupational housewife's hand eczema among housewives attending Baquba Teaching Hospital /outpatient. Self-administered questionnaire which included occupational and sociodemographic variables was used and clinical examination has been done by dermatologist. Result: The prevalence of occupational housewife's hand eczema in patients with atopy was (62.3%). The most common age group was (18- 37) years (75%), the younger age group. The duration of work was < (7) years. Roughness, fissures and erythema form more than (79%) of the cases. The most common sites of the lesions appeared mostly on palms and ventral surface of the fingers (63.5%). More than 90% of the cases did not used protective measures during work. Conclusion: The occupational housewife's hand eczema are frequently involved in patients with active atopic dermatitis. This study concluded that housewife's hand eczema is typically a lifestyle-related skin disease. Irrespective of any predisposition, its development and exacerbation depend on a patient’s awareness of causative and preventative factors.